(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The Flipped Classroom model restructures the learning process by shifting direct instruction to pre-class activities and dedicating class time to active learning. Its growing implementation in higher education aims to enhance student autonomy and critical thinking. However, challenges such as insufficient student preparation, low-quality pre-class materials, and misalignment of assessments hinder its effectiveness. This article proposes methodological improvements to enhance the flipped classroom model to support independent learning. Recommendations include scaffolding pre-class content, designing higher-order in-class activities, integrating formative assessments, and training students in self-regulated learning. These practices contribute to improved engagement, deeper learning, and stronger academic outcomes in higher education.